Conservatively Treated Femoral Intertrochanteric Fracture With Early Asymptomatic Novel Coronavirus Disease 2019 (COVID-19): A Case Report. (27th October 2020) - Suzuki, Yuki; Kasashima, Toshihiko; Hontani, Kazutoshi; Yamamoto, Yasuhiro; Ito, Kanako; Xu, Liang; Matsuoka, Masatake; Iwasaki, Koji; Onodera, Tomohiro; Kondo, Eiji; Iwasaki, Norimasa
Introduction: The ongoing outbreak of novel coronavirus disease 2019 (COVID-19) is a worldwide problem. Although diagnosing COVID-19 in fracture patients is important for selecting treatment, diagnosing early asymptomatic COVID-19 is difficult. We describe herein a rare case of femoral intertrochanteric fracture concomitant with early asymptomatic novel COVID-19. Case presentation: An 87-year-old Japanese woman was transferred to our emergency room with a right hip pain after she fell. She had no fever, fatigue, or respiratory symptoms on admission and within the 14 days before presenting to our hospital, and no specific shadow was detected in chest X-ray. However, chest computed tomography (CT) was performed considering COVID-19 pandemic, and showed ground-glass opacities with consolidation in the dorsal segment of the right lower lung field. Then, qualitative real-time reverse-transcriptase-polymerase-chain-reaction (RT-PCR) was carried out and turned out to be positive. She was diagnosed right femoral intertrochanteric fracture with concomitant COVID-19 infection. Conservative treatment was applied to the fracture due to infection. After admission, fever and oxygen demand occurred but she recovered from COVID-19. Throughout the treatment period, no cross-infection from the patient was identified in our hospital. Conclusion: This case highlights the importance of considering chest CT as an effective screening method for infection on hospital admission in COVID-19-affected areas, especially in trauma patients with early asymptomatic novel COVID-19.